Faculty of Islamic Economics and Business Students’ Second Language Acquisition on Arabic through Hybrid and Receptive Learning Models - Putra, Wahyu Hanafi; Zaini, Hisyam; Holilulloh, Andi; Ahmed Shalabi, Essam Mustafa; Salma, Kunti Nadiyah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research aims to analyze the ability of students at the Faculty of Islamic Economics and Business (FEBI) IAIN Ponorogo to master Arabic as a second language through hybrid and sensory learning activities. This qualitative research with a case study type was done toward 176 students, with a sample of 20 students as the research population. The sampling technique was carried out using non-probability sampling with the snowball sampling method because the samples were taken based on the needs of this research. The research data is in the form of pronunciation of vocabulary sounds, spelling of Arabic letters, verbs and nouns, understanding the material being listened to, and reading Arabic texts of FEBI IAIN Ponorogo students in the odd semester of 2022/2023 academic year. The student reading source used in the research is the book